Cooperative enhancement versus additivity of two-photon-absorption cross sections in linear and branched squaraine superchromophores. Issue 24 (6th June 2016) - Ceymann, Harald; Rosspeintner, Arnulf; Schreck, Maximilian H.; Mützel, Carina; Stoy, Andreas; Vauthey, Eric; Lambert, Christoph
Abstract : Our investigation of the nonlinear optical properties of a series of oligomeric squaraine dyes showed enhanced cross sections for linear oligomers but only additivity for branched systems. Abstract : The linear and nonlinear optical properties of a series of oligomeric squaraine dyes were investigated by one-photon absorption spectroscopy (1PA) and two-photon absorption (2PA) induced fluorescence spectroscopy. The superchromophores are based on two indolenine squaraine dyes with transoid (SQA) and cisoid configuration (SQB). Using these monomers, linear dimers and trimers as well as star-shaped trimers and hexamers with benzene or triphenylamine cores were synthesised and investigated. The red-shifted and intensified 1PA spectra of all superchromophores could well be explained by exciton coupling theory. In the linear chromophore arrangements we also found superradiance of fluorescence but not in the branched systems. Furthermore, the 2PA showed enhanced cross sections for the linear oligomers but only additivity for the branched systems. This emphasizes that the enhancement of the 2PA cross section in the linear arrangements is probably caused by orbital interactions of higher excited configurations.